Flory–Huggins modeling of thermodynamic asymmetry in molten Hg–Na and Hg–Pb amalgams - Acharya, Basant; Koirala, Ishwar (Himalayan Physics, 2026)
This study applies the Flory-Huggins model to HgNa and HgPb amalgams at 673 K and 600 K, respectively, to compute thermodynamic functions including Gibbs free energy, entropy, enthalpy of mixing, and activities. Predictions are validated against experimental data from Hultgren et al. (vapor pressure, calorimetry, electrochemistry).The HgNa system exhibits strongly negative interaction energy (μ = -9756 cal/mol) and exothermic enthalpy, indicating preferential heterocoordination, while HgPb shows positive interaction energy (μ = +831 cal/mol) with entropy-driven mixing. Both systems display asymmetric thermodynamic profiles arising from significant atomic size mismatches (φ = 0.62 for Hg-Na, φ = 0.81 for Hg-Pb). The Flory-Huggins model demonstrates excellent predictive capability withcorrelation coefficients R² > 0.996, successfully capturing composition-dependent asymmetries that the Regular Solution model cannot describe. This work establishes the Flory-Huggins approach as superior for systems with substantial size differences, providing valuable insights for amalgam design and high-temperature solution thermodynamics. This validates Flory-Huggins as superior for size-mismatched alloys, aiding amalgam design.